School Projects in Sciences at the Lower Secondary Schools - Czech-Slovak Comparative Research - Pouchová, Milena (Scientia in educatione, 2013)
The article deals with the current state of using school projects in the teaching of sciences at lower secondary schools. It includes some results of Czech-Slovak comparative research based on a questionnaire survey of June 2009 aimed at a randomly selected sample of 180 Czech and 71 Slovak schools. The goal of the research was to find out to what extent project teaching is currently used and thus build a basis for other more focused research. The survey focused on the number and basic characteristics of carried out projects (e.g., length, the number of school subjects, classes and teachers), on some activities of teachers and pupils within the projects and also on the teachers’ attitudes towards this way of teaching.